Effect of Competence of Financial Administration Officials, Internal Control System, and Financial Supervision of Financial Reporting Information - Rahmawati Rahmawati; Pirmansyah Pirmansyah; Helmiat Helmiat; Maulina Maulina; Wadri Wahyu; Hendrio Hendrio (Greenation International Journal of Economics and Accounting, 2023)
This research was conducted for 2 (two) months from July to August 2022. The sample in this study was 96 respondents. The data analysis technique uses SPSS Version 25. Based on a partial test of the competency variable of financial administration officer(X1), the government internal control system variable(X2) has a significant effect, and the Regional financial supervision variable(X3) has no significant effect on local government financial statements information(Y). Meanwhile, the results of the simultaneous test on the competency variables of financial administration officer, the government's internal control system and regional financial supervision have proven to have a significant effect on local government financial statements information. The closeness of the relationship that occurs between the competence of financial administration officials, the Government's internal control system, regional financial supervision of Regional Government Financial Reporting Information is moderate in the form of a correlation coefficient (R) of 54.2%. While the contribution of the independent variable to the dependent variable is 27.0%, the remaining 73.0% is determined by other variables not included in this research model.